A Descriptive Study to Assess the Knowledge and Attitude Towards HPV Vaccination among Students of Selected School at Ludhiana Punjab (International Journal of Nursing Education, 2019)
Introduction: Cervical cancer is the third most commonly diagnosed cancer worldwide and fourth leading cause of cancer in women. HPV is the most common sexually transmitted infection (STI).. But there are vaccines that can stop these health problems from happening. Aim: The study was carried out to assess the knowledge and attitude towards HPV vaccination among students of school. Methodology: A descriptive research design was used to assess the attitude and knowledge of 60 students in selected school by sampling techniques who were studying in the school of Ludhiana, Punjab. A self structured questionnaire tool was used to assess the knowledge and attitude with method. Results: It shows that 3% of students having good knowledge (5%) and 46% of students having average knowledge (76.6%) and 11% of students having poor knowledge (18.3%). This study shows that 49% of the students having unfavourable attitude (81.6%) and remaining 11%o the student having favourable attitude (18.3%) regarding HPV vaccination. Conclusion: Hence, it is concluded that the majority of students having average knowledge and majority of student having unfavourable attitude towards HPV vaccination.
Keywords: Assess, knowledge, attitude, HPV Vaccination, School students